Glocal architecture - Константин Лидин (Russian Academy of Architecture and Construction Sciences, 2021)
The article examines the concept of glocality in relation to architecture and urban planning. The notion of glocality is proposed as an embodiment of global trends in local forms, taking into account the historical, geographical and cultural characteristics of the given chronotope. The deviation of the balance towards globality leads to unification, erasure of local features and loss of cultural diversity. On the contrary, the predominance of the local aspect leads to "cultural nationalism", separation from the global information space and artistic barrenness.